2y^2 - 3y - 6 = 0 a = 2, b = -3, c = -6 b^2 - 4ac = (-3)^2 - 4(2)(-6) = 9 + 48 = 57 y = [-b ± sqrt (b^2 - 4ac)]/2a = (3 ± sqrt 57)/4
Question
Updated 7/8/2014 8:46:31 AM
Rating
3
2y^2 - 3y - 6 = 0
a = 2, b = -3, c = -6
b^2 - 4ac = (-3)^2 - 4(2)(-6) = 9 + 48 = 57
y = [-b ± sqrt (b^2 - 4ac)]/2a
= (3 ± sqrt 57)/4
Confirmed by andrewpallarca [7/8/2014 8:50:46 AM]

27,948,369
*
Get answers from Weegy and a team of really smart live experts.
Popular Conversations
The need for blank. Complicate information sharing among emergency ...
Weegy: The need for Advanced Equipment can complicate information sharing among emergency personnel. User: The MAC ...
for a sound with low pitch what else is always low
Weegy: Pitch. ... Low-pitched sounds come from things that vibrate more slowly. Humans can hear sounds of different ...
S
L
P
C
Points 605 [Total 1649] Ratings 2 Comments 585 Invitations 0 Offline
S
R
L
R
P
R
P
R
R
R
R
P
R
P
Points 485 [Total 2494] Ratings 4 Comments 445 Invitations 0 Offline
S
L
Points 405 [Total 551] Ratings 3 Comments 375 Invitations 0 Offline
S
Points 33 [Total 33] Ratings 1 Comments 23 Invitations 0 Offline
S
Points 20 [Total 20] Ratings 2 Comments 0 Invitations 0 Offline
S
L
R
P
Points 18 [Total 1381] Ratings 0 Comments 18 Invitations 0 Offline
S
Points 12 [Total 12] Ratings 0 Comments 2 Invitations 1 Offline
S
Points 11 [Total 11] Ratings 1 Comments 1 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.